Differentiation and Positioning Strategy: A Toss of the Same Coin - Akpoyomare, Oghojafor Ben; Adeosun, Ladipo Patrick Kunle; Ganiyu, Rahim Ajao (International Journal of Management and Sustainability, 2012)
The increasing rate of the incidence of globalization of market, and the attendant intense competition amongst local business organizations in rapidly developing economies has taken a shift from price competition strategy (to avoid price war) to non-price competition strategy in terms of product/service differentiation and positioning to achieve the same objectives of preventing declining sales-turnover, profitability, and market-share and by extension secure market/competitive advantage over competitors. Differentiation and positioning have each been separately discussed in marketing literature; however, this paper represents an attempt to view same as a toss of the same coin.